Stimulasi perkembangan otak janin di dalam kandungan selama kehamilan di Desa Jogoroto, Kecamatan Jogoroto, Kabupaten Jombang - Nur Laila Faizah; Kolifah; Bherty, Chanda Paramitha (Journal of Health Innovation and Community Services, 2023)
Stimulation of the fetal brain is closely related to efforts to prepare the nation's next generation, especially creating a generation of quality, with adequate intelligence potential in preparing themselves to face a competitive life. This community benefit is carried out with the point of expanding information and hone of fortifying the baby in an exertion to progress the quality of the brain within the hatchling so as to enable an increment within the potential for insights in children. This community benefit takes the frame of a arrangement of exercises enduring 6 months, of course carried out by complying with the 8 standards of security and complying with wellbeing conventions to anticipate the transmission of Covid-19.As a result of the community benefit of 30 pregnant ladies who gone to, 89% of pregnant ladies at first did not get it the incitement of fetal brain advancement amid pregnancy. At that point assess the comes about of the consider of 30 pregnant ladies who were display. 97% of pregnant women already understood the stimulation of fetal brain development from the womb during pregnancy. The community service activity entitled Stimulation of fetal brain development from the womb during pregnancy. In Jogoroto Village, Jogoroto District, Jombang Regency, midwifery science has been implemented in a community service activity